2016
DOI: 10.1117/1.jrs.10.036009
|View full text |Cite
|
Sign up to set email alerts
|

Lidar observations of long-range transported Saharan dust over Sofia, Bulgaria: a case study of dust mixed with local aerosols

Abstract: .Two-wavelength (1064/532  nm) lidar observations of long-range transported Saharan dust present in the atmosphere over Sofia, Bulgaria, during a 4-day dust intrusion event in winter 2010, are reported. Aged desert aerosols are detected at altitudes up to 4 km above the sea level, within and above the boundary layer as mixed with other aerosols—representing the particular case under consideration. Optical, microphysical, and dynamical properties of dust aerosols are obtained and analyzed. Special attention is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 69 publications
3
16
0
Order By: Relevance
“…The wintertime Saharan dust events presented and discussed were studied by means of an aerosol lidar designed and built in the LRL. 8,12,43 The lidar system is configured in a mono-static biaxial alignment pointing at an angle of 32 deg with respect to the horizon, as determined by its position in the lab. Therefore, although signals from as far as 30 km can be recorded, the maximum sounding height is limited to about 16 km.…”
Section: Measurement Site Instrumentation and Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The wintertime Saharan dust events presented and discussed were studied by means of an aerosol lidar designed and built in the LRL. 8,12,43 The lidar system is configured in a mono-static biaxial alignment pointing at an angle of 32 deg with respect to the horizon, as determined by its position in the lab. Therefore, although signals from as far as 30 km can be recorded, the maximum sounding height is limited to about 16 km.…”
Section: Measurement Site Instrumentation and Methodsmentioning
confidence: 99%
“…3 Huge amounts of airborne desert dust are frequently transported north-eastward to the Mediterranean and Europe each year. [4][5][6][7][8][9][10][11][12][13] Intrusions of Saharan dust over Europe mostly take place in spring and summer, as observations by ground-based and air/space-born apparatus have shown. In winter, the European continent is predominantly invaded by cold frontal systems from the north; therefore, events of desert dust transport are less probable and, as a rule, rare.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the fact that lightscattering characteristics of aerosol particles were altered after up-taking water vapor, Tong Wu et al [32] studied the aerosol hygroscopic growth from micropulse Lidar. A long-range transported Saharan dust over Sofia, Bulgaria was detected by two-wavelength (1064/532 nm) Lidar including the optical, microphysical, and dynamical properties of dust aerosols at different stages [33]. The results shown that the dust backscatter-related Angstrom exponents (BAEs) values were in the range of 0.3 to 0.6 (±0.2), which indicated domination of coarse particles in the micron size range.…”
Section: Introductionmentioning
confidence: 98%